Quasi-periodic dipping in the ultraluminous X-ray source, NGC 247 ULX-1. Issue 3 (25th May 2021) - Alston, W N; Pinto, C; Barret, D; D'Aì, A; Del Santo, M; Earnshaw, H; Fabian, A C; Fuerst, F; Kara, E; Kosec, P; Middleton, M J; Parker, M L; et al.
ABSTRACT: Most ultraluminous X-ray sources (ULXs) are believed to be stellar mass black holes or neutron stars accreting beyond the Eddington limit. Determining the nature of the compact object and the accretion mode from broad-band spectroscopy is currently a challenge, but the observed timing properties provide insight into the compact object and details of the geometry and accretion processes. Here, we report a timing analysis for an 800 ks XMM–Newton  campaign on the supersoft ultraluminous X-ray source, NGC 247 ULX-1. Deep and frequent dips occur in the X-ray light curve, with the amplitude increasing with increasing energy band. Power spectra and coherence analysis reveals the dipping preferentially occurs on ∼5 and ∼10 ks time-scales. The dips can be caused by either the occultation of the central X-ray source by an optically thick structure, such as warping of the accretion disc, or from obscuration by a wind launched from the accretion disc, or both. This behaviour supports the idea that supersoft ULXs are viewed close to edge-on to the accretion disc.